Mechanisms of transformation of nicotinamide mononucleotides to cerebral infarction hemorrhage based on MCAO model - Shu, Liang (Saudi J Biol Sci, 2020)
OBJECTIVE: The study aims at discussing the effect of nicotinamide mononucleotides on protecting hemorrhagic transformation of cerebral infarction in the middle cerebral artery occlusion (MCAO) model. METHOD: Male mice aged 4–5 weeks and weighing about 22–35 g in Shanghai Ninth People’s Hospital are divided into three groups: sham group, collagenase intracerebral hemorrhage model (cICH + Vehicle) group and collagenase nicotinamide mononucleotide (cICH + NMN) group. Then, the intervention therapy research is carried out. After 24 h, the neurological function, brain edema, hematoma volume, body weight, hemorrhage volume, RNA expression level, apoptosis, inflammatory factors and reactive oxygen species (ROS) content in surrounding tissues of mice are analyzed comprehensively. RESULTS: Compared with the other two groups, nicotinamide mononucleotides in MCAO model have significant effects on improving neurological function, brain edema, inflammatory factors, body weight and cell apoptosis in mice, but have no significant effect on hemorrhage volume and hematoma volume in mice. CONCLUSION: Nicotinamide mononucleotides can significantly improve the collagenase-induced intracerebral hemorrhage (ICH) model in mice under MCAO model, and they can protect the brain tissue of mice from RNA level to tissue cell level or mouse body weight and volume level.